The tropics and the traveling gaze : India, landscape, and science, 1800-1856 - Arnold, David, 1946- (Culture, place, and nature., 2006)
"The Tropics and the Traveling Gaze considers the European representation and understanding of landscape and nature in early nineteenth-century India. It draws on travel narratives, literary texts, and scientific literature to show the diversity of European (especially British) responses to the Indian environment and the ways in which these contributed to the wider colonizing process."--Jacket